American cutaneous leishmaniasis associated with degradation of native forest, regardless of economic, social and infrastructure vulnerability. (19th December 2020) - Caldart, Eloiza Teles; Sevá, Anaiá da Paixão; Pinto‐Ferreira, Fernanda; Pereira Pachoal, Aline Ticiani; de Oliveira, Juliana Silva; Cortela, Isadora de Britto; Bernardes, Juliana Correa; Freire, Roberta Lemos; Mistsuka‐Breganó, Regina; Navarro, Italmar Teodorico
Abstract: American cutaneous leishmaniasis (ACL) is a notifiable dermatozoonosis with relevant morbidity. The present study aimed to evaluate the epidemiological aspects of cases of ACL reported in Northern Paraná (2007–2016), as well as to georeference and analyse the influence of economic, social and environmental variables. Data from ACL notification forms were obtained and the patients' houses were georeferenced. Descriptive statistics, calculations of disease incidence and proportion of vegetation cover by municipality, spatial analysis, multiple linear regression and vulnerability analysis by census sector (CS) were performed. One thousand four hundred fifty‐one cases of ACL were reported in the 89 municipalities of four regional health (RH). The average incidence of cases per 10, 000 inhabitants was as follows: 11.58, 8.79, 4.92 and 4.03 in 18thRH, 15thRH, 16thRH and 17thRH. Peaks of incident cases were observed in 2008, 2012 and 2015. There was a statistically significant difference between the HR when comparing the proportions of the variables gender, age, education level, area of residence, clinical form, diagnostic criteria, response to treatment and drug used in case of failure. It was observed that the lower the proportion of remaining Atlantic Forest, the greater the incidence of ACL in the municipality. With regard to clusters analysis, treatment abandonment clusters were observed in the 15thRH and mucous form clusters were observed in the 15thRH, 16thRH and 17thRH. The vulnerability analysis by CS allowed us to observe a statistically significant difference in all vulnerability indicators: economic and social in 15thRH and 17thRH; home infrastructure in 15thRH and 18thRH, urban infrastructure in 15thRH and 18thRH and compound vulnerability index in 15thRH and 18thRH. However, the most vulnerable areas did not always have the highest number of cases. The data presented demonstrate that preventive and health education measures must be mainly directed to areas of greater degradation of native forest; regardless of the vulnerability situation.